Faktor Kepuasan Pasien Terhadap Waste Makanan Lunak Pada Pasien Diabetes Melitus Di Rs. Muhammadiyah Gresik - Siti Juwariyah; Dwi Novri Spriatiningrum; Sutrisno Adi Prayitno (Ghidza Media Jurnal, 2019)
ABSTRACT This study aims to determine the factors associated with the occurrence of soft food waste from adult inpatient DM patients. The type of this research is explanatory research with a cross sectional research design survey method. The population of adult DM inpatients are 28 people. The technique of selecting samples by simple random sampling. Data were analyzed by the Rank Spearman. The instruments used were questionnaires, scales and food waste observation for ms. The results showed that the factors related to the waste were the accuracy of pre food preparation schedule (p = 0.352) post (= 0.604), pre food quality (p = 0.010) post (0.787), the completeness and cleanliness of pre food equipment (p = 0.009) post (p = 0.054), attitude and appearance of pre renderers (p = 0.022) post (p = 0.466), pre satisfaction level (p = 0.416) post (p = 0.416). The results of the pre-study show that there are no corelation between the food serving schedule with DM waste and has a medium strength correlation category. The results of post study show that there are no correlation between the accuracy of the food schedule, food quality, renderers attitude and the level of satisfaction with the occurrence of DM patient waste, there is a corelation between equipment hygiene completeness with DM patient waste. Keywords: Diabetic patients, soft foods, food waste, quality service level of satisfaction ABSTRAK Tujuan penelitian ini adalah untuk mengetahui faktor yang berhubungan dengan terjadinya sisa makanan lunak pada pasien DM rawat inap dewasa. Jenis penelitian ini adalah eksplanatory research dengan metode survei desain penelitian cross sectional. Populasi pasien DM rawat inap dewasa sebanyak 28 orang. Teknik pemilihan sampel dengan cara simple random sampling. Data dianalisis menggunakan uji Rank Spearman. Instrumen yang digunakan adalah kuesioner, timbangan dan formulir pengamatan sisa makan. Hasil penelitian menunjukkan bahwa faktor yang berhubungan dengan waste yaitu ketepatan jadwal penyajian makanan pre (p=0,352) dan post (=0,604), mutu makanan pre (p=0,010) dan post (0,787), kelengkapan dan kebersihan peralatan makan pre (p=0,009) dan post (p=0,054), sikap dan penampilan penyaji pre (p=0,022) dan post (p=0,466), tingkat kepuasan pre (p=0,416) dan post (p=0,416). Hasil penelitian pre menunjukkan bahwa tidak ada hubungan antara jadwal penyajian makanan dengan waste DM dan memiliki kategori kekuatan hubungan sedang. Hasil penelitian post menunjukkan bahwa tidak ada hubungan antara ketepatan jadwal makanan, mutu makanan, sikap penyaji dan tingkat kepuasan dengan terjadinya waste pasien DM, ada hubungan antara kelengkapan kebersihan peralatan dengan waste pasien DM. Kata Kunci : Pasien diabetes, Tingkat Kepuasan, Waste, Makanan Lunak.